Glechon spathulata Benth.: estudo fitoquímico e biológico - Kunz, Vanessa Teixeira (2007)
The main groups of secondary metabolites of Glechon spathulata Benth. were evaluated by a phytochemical screening and the volatile oil obtained by hydrodistillation was analyzed by GC-MS. Volatile oil, ethanolic crude extract and hexanic, chloroformic, ethyl acetate and butanolic fractions of G. spathulata were submitted to the lethality test against Artemia salina Leach., to the antimicrobial activity by bioauthographic assay and broth microdilution. Antioxidant activity by DPPH in thin-layer chromatography (TLC) and spectrophotometric assay were also evaluated. Flavonoids, tannins, sterols and/or triterpenoids, saponins, anthocyanic pigments, volatile and fixed acids were found in G. spathulata. The GC of the oil revealed the presence of 9 constituents. All samples presented Artemia salina toxicity (LC50<1000 μg/ml). The volatile oil showed antimicrobial activity evaluated by bioauthographic assay against Gram-positive and Gram-negative bacteria and against Candida albicans, the crude extract didn t show activity against the tested microorganisms in same conditions of assay with volatile oil. Volatile oil, hexanic and ethyl acetate fractions showed good inhibitory activity against Gram-positive and Gram-negative bacterial cultures. Through DPPH method all the samples showed antioxidant activity by TLC, by spectrophotometric method, ethyl acetate, butanolic fractions and volatile oil showed excellent antioxidant activity with IC50 7,99 μg/ml; 11,75 μg/ml and 20,59 μg/ml respectively.